Nephrotoxicity in patients receiving immune checkpoint inhibitors - Chuva,Teresa (2019)
Over the last years, immunotherapy has become part of the most important strategies to treat some types of cancer. Immune checkpoint inhibitors are within this new class of drugs and consist of monoclonal antibodies that target inhibitory receptors expressed on T cells. While revolutionary results have been achieved with these therapies, their widespread use has also brought to light multiple immune-related adverse effects that impact the patients quality of life and survival, posing new challenges to clinicians. The kidney is one of the affected organs, and nephrotoxicity has probably been underestimated in the first clinical trials. The etiopathogenic mechanisms involved and the management of renal disease in this context are not fully known. This review aims to illustrate the most recent data on the clinical presentation, diagnosis, treatment, and behavior of patients with kidney complications of immune checkpoint inhibitors, including particularly vulnerable subjects, such as transplant recipients. A growing number of patients are being handled with these drugs, and nephrologists are expected to be part of the multidisciplinary approach required by the new immunotherapies